2021
DOI: 10.1017/wsc.2021.22
|View full text |Cite
|
Sign up to set email alerts
|

Weedy rice (Oryza spp.): what’s in a name?

Abstract: There are two species of cultivated rice in the world - Oryza sativa L. from Asia and O. glaberrima from Africa. The former was domesticated from the wild progenitor, O. rufipogon and the latter from the African wild rice species O. barthii. The first known center of rice cultivation in China generated the O. sativa subspecies japonica. The indica subspecies arose from the second center of domestication in the Ganges River plains of India. Variants of domesticated lines and the continuous hybridization between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…Of the wild rice relatives, more WR biotypes are highly similar to O. rufipogon. The common wild rice (O. rufipogon) has been found to contribute to the evolution of sympatric weedy rice in South and Southeast Asia, however, studies do not show direct evolution of WR from O. rufipogon, indicating crop-wild hybridization (reviewed by Burgos et al, 2021). In Malaysia and Thailand, studies on WR using SSRs and SNPs revealed natural gene flow and hybridization between known wild rice and cultivated rice as the major causes of occurrence and spread of WR biotypes (Pusadee et al, 2013;Song et al, 2014;Neik et al, 2019;Vigueira et al, 2019;Wedger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the wild rice relatives, more WR biotypes are highly similar to O. rufipogon. The common wild rice (O. rufipogon) has been found to contribute to the evolution of sympatric weedy rice in South and Southeast Asia, however, studies do not show direct evolution of WR from O. rufipogon, indicating crop-wild hybridization (reviewed by Burgos et al, 2021). In Malaysia and Thailand, studies on WR using SSRs and SNPs revealed natural gene flow and hybridization between known wild rice and cultivated rice as the major causes of occurrence and spread of WR biotypes (Pusadee et al, 2013;Song et al, 2014;Neik et al, 2019;Vigueira et al, 2019;Wedger et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The seemingly recurrent genetic evolutions of WR have spurred several nonmutually exclusive hypotheses on the possible origins, according to Burgos et al (2021): a) de-domestication of cultivated rice (Kanapeckas et al, 2016;Li et al, 2017;Qiu et al, 2017), b) intervarietal hybridization among cultivated rice cultivars (Pusadee et al, 2013;Qiu et al, 2014;Ishikawa et al, 2005), c) crop-wild hybridization between domesticated and wild rice (Pusadee et al, 2013;Song et al, 2014); and d) wild-derived origin from wild ancestors adapted in rice areas (Huang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…is recognised as the most competitive and significantly reduces rice yields even at small densities (Smith, 1988). Weedy rice control is very difficult due its similarities with rice associated with its origin and resilience to environmental factors (for review see Burgos et al, 2021). Weedy rice is of taller height and easy shattering, have high seed dormancy and often pigmented seeds (Burgos et al, 2014; Durand‐Morat et al, 2018; Engku et al, 2016; Fogliatto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Weedy rice is of taller height and easy shattering, have high seed dormancy and often pigmented seeds (Burgos et al, 2014; Durand‐Morat et al, 2018; Engku et al, 2016; Fogliatto et al, 2011). These traits make weedy rice competitive and persistent and highly difficult to control, leading up to 90% in rice harvest losses, increases in soil seed reservoir and decreases in rice grain price due to contamination (reviewed by Burgos et al, 2021; Nadir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…When present, weedy rice is the most difficult weed to control in rice because its biological traits are nearly identical to those of cultivated rice. When not controlled, weedy rice is one of the most economically damaging rice weeds globally, due to severe yield losses (reviewed in Roma- Burgos et al 2021) and reduction of grain quality (Ottis et al 2005). In Arkansas, weedy rice is deemed the third most problematic weed in rice, behind Echinochloa spp.…”
Section: Introductionmentioning
confidence: 99%